Efficacy of auditory training in older adults by electrophysiological tests - Moossavi, Abdollah; Aghazadeh, Jafar (Shinavāyi/shināsi-i, 2019)
Background and Aim: Most elderly people in noisy environments complain of speech comprehension. At present, hearing aids or cochlear implants are the main treatment options. However, these devices merely enhance sound audibility and do not compensate for central processing changes caused by aging, hearing loss, or cognitive decline. This article reviewed plasticity topic in the auditory system and the use of auditory evoked potentials to prove the effectiveness of auditory training. Recent Findings: The search for relevant articles in the Google Scholar, PubMed, Springer, and ProQuest databases was conducted with the keywords of “auditory education,” “electrophysiology,” “plasticity,” and “aging.” A total of 107 articles were found with these keywords, and finally, 98 articles, published between 1977 and 2018, were used. Existence of plasticity in the central auditory system, regardless of age, has been proven. Therefore, cognitive and auditory training to reduce cognitive problems and improve central hearing processing in appropriate cases can positively affect the quality of hearing and social communication of the elderly. Because efficacy is an important component of any therapeutic approach, the assessment of the benefits of hearing training can be demonstrated by electrophysiological tests. Conclusion: Auditory training may play an important role in the elderly treatment program with speech perception defects. The usefulness of this rehabilitation can be objectively evaluated through cortical and subcortical electrophysiological methods.